Students’ perceptions of ‘Online’ flipped classroom during COVID-19 Pandemic - Mohamed Azmin, Nor Fadhillah; Abd Wahab, Mohd Firdaus; Ahmad, Farah; Asnawi, Ani Liza; Jusoh, Ahmad Zamani; Ibrahim, Siti Noorjannah; Jimat, Dzun Noraini (2021)
The COVID-19 pandemic has forced several sectors to either cease operations or make changes in approaches including the educational sector. The education sector faces sudden transition to online learning as a result of COVID-19 has unearthed some benefits as well as challenges. At the early phase of the pandemic, educators all over the world are bombarded with webinars and workshops on the topics of designing and conducting online teaching and learning. However, the is almost no of webinars or workshops on similar topics targeting the students, hence the preparedness and readiness of the students remain unclear. In this study, we focus on understanding the Biochemical Engineering students’ perception of their adoption and acceptance of flipped classroom approach during the pandemic. Responses were collected from students of Year 2, 3 and 4; out of four years of study. The finding of this study indicated that flipped classroom approach can resulted in ineffective online learning environment if it is not designed carefully.